Design of a Circular Polarized Printed Rectenna for Satellite Solar Power Station Array Construction - Kumar, Deepak; Chaudhary, Kalpana (International Journal of Engineering and Technology, 2018)
A circularly polarized single feed microstrip patch antenna with voltage doubler rectification is designed at 2.45 GHz for satellite solar wireless power transfer application. A bandpass filter is also designed and combined with an antenna that will efficiently eliminate signal harmonics up to third order. An HSMS-8202 microwave zero-bias Schottky barrier diodes accessible in SOT 23 package as the series pair is utilized in the proposed rectenna design. The rectenna has a high conversion efficiency of 70%. The printed rectenna can be interconnected to construct the rectenna arrays.Â Â